Comparative Behavior of Wild and Hatchery Reared White Sea Bream (Diplodus sargus) Released on Artificial Reefs Off the Algarve (Southern Portugal) - Lino, P. G. (2016)
Three hatchery produced and reared (HPR) and five wild white sea bream (Diplodus sargus) were double tagged with Vemco V8SC-2L acoustic transmitters and Floy Tag T-bar anchor tags, and released on artificial reefs located near a natural reef off the southern coast of Portugal. Passive telemetry was used to monitor movements of the white sea bream over a nine week period from April to June 2007. Differences in behavior at release, habitat association (artificial vs. natural reef), and in daily movements were registered. Wild fish moved from one habitat to the other with increased preference for the artificial habitat during the day, whereas HPR fish showed no site fidelity or consistent daily movement pattern and left the release site soon after release. Comparison of Minimum Convex Polygon (MCP) showed a higher area usage by wild fish. This experiment shows that these artificial reefs are used on a daily basis by wild white sea bream but apparently are not optimal release locations for hatchery produced white sea bream.